2016
DOI: 10.1088/1748-3190/11/3/036007
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic ultrasonic emitter inspired by horseshoe bat noseleaves

Abstract: The emission of biosonar pulses in horseshoe bats (family Rhinolophidae) differs from technical sonar in that it has dynamic features at the interface to the free field. When the horseshoe bats emit their biosonar pulses through the nostrils, the walls of a horn-shaped baffle (anterior leaf) are in motion while diffracting the outgoing ultrasonic wave packets. Here, biomimetic reproductions of the dynamic emission shapes of horseshoe bats have been studied for their ability to impose time-variant signatures on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…In accordance with (iv), noseleaf and pinna deformations in horseshoe bats have been predicted to produce qualitative beampattern changes [15,17,20]. Similar changes have been demonstrated experimentally with biomimetic reproductions of noseleaves [21] and pinnae [10,22]. In these experiments, the shape deformations resulted in time-variant device characteristics [21,23].…”
supporting
confidence: 73%
See 2 more Smart Citations
“…In accordance with (iv), noseleaf and pinna deformations in horseshoe bats have been predicted to produce qualitative beampattern changes [15,17,20]. Similar changes have been demonstrated experimentally with biomimetic reproductions of noseleaves [21] and pinnae [10,22]. In these experiments, the shape deformations resulted in time-variant device characteristics [21,23].…”
supporting
confidence: 73%
“…Similar changes have been demonstrated experimentally with biomimetic reproductions of noseleaves [21] and pinnae [10,22]. In these experiments, the shape deformations resulted in time-variant device characteristics [21,23]. In the frequency domain, the beampatterns typically alternated between a concentration of sensitivity in a single mainlobe and scattering among local maxima (sidelobes) [10,17].…”
supporting
confidence: 68%
See 1 more Smart Citation
“…Hence, these motions could change the acoustic characteristics of the biosonar emission and reception during a single pulse or a single echo. Indeed, such changes have been predicted by numerical analysis (Gao et al 2011;He et al 2015) and demonstrated with biomimetic physical prototypes Fu et al 2016). Time variant acoustic characteristics would allow the bats to sense their environments through "multiple views" and hence could enhance the quantity -and perhaps also the quality -of the sensory information available to the animals.…”
Section: Dynamic Information Encoding: Noseleaf and Pinna Motionsmentioning
confidence: 96%
“…One of the differences between technical and biosonar that has been observed and studied in literature since has been the dynamics of the biosonar system [3,26,25,9]. This has been of particular interest due to the novelty of the idea: bending the biosonar apertures to dynamically alter a sonar signal [3].…”
Section: Bats and Biosonarmentioning
confidence: 99%